THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, FINANCIAL COMPENSATION AND GENDER ON JOB SATISFACTION OF CARGO TERMINAL BRANCH OF MINANGKABAU INTERNATIONAL AIRPORT - Zaki, Muhammad; Andriani, Chichi (Human Resource Management Studies, 2023)
Objective -This research is to find out: (1) The effect of transformational leadership on job satisfaction at Minangkabau Airport Cargo Terminal (2) The effect of financial compensation on job satisfaction at Minangkabau Airport Cargo Terminal (3) The Effect of Gender on job satisfaction at Minangkabau Airport Cargo Terminal Methodology –This research is a quantitative research. The population of this study were all employees working at the Minangkabau International Airport Cargo Terminal as many as 41 people. The sampling technique was carried out by using Technic Total Sampling, which is a sample selection method that is applied to the entire population. Collecting data using a questionnaire with a Likert scale. The data analysis technique is a regression analysis technique using the SPSS V. 25 application. Results -The results of data processing in this study show that: (1) There is a positive influence between transformational leadership on job satisfaction. (2) Compensation has a significant and positive effect on job satisfaction at Minangkabau Airport Cargo Terminal. (3) there is a positive influence between gender on job satisfaction.